Investigation on Chassis Dynamometer with Capability to Test Regenerative Braking Function - Nurul Azwa Othman; Hamdan Daniyal (Institute of Advanced Engineering and Science, 2015)
An investigation-based approach to a bidirectional power flow method for testing regenerative braking function on a chassis dynamometer is presented. The requirements and specifications for capability to test regenerative braking function of Electric Vehicle (EV) emulated by using a bidirectional chassis dynamometer are discussed. The dynamometer emulates road load conditions during testing, and regenerative braking is able to test their function while the vehicle is in deceleration condition. Performances of power requirement are illustrated and translated into sequence diagram. It is shown that the proposed topology is particularly advantageous in generating and regenerating power for energy consumption. The overview of conventional chassis dynamometer and the proposed chassis dynamometer is compared to investigate the parameter in the development of regenerative braking test.